Numerical implementation of a multiaxial cyclic plasticity model for the Local Strain Method in low cycle fatigue (Fracture and Structural Integrity, 2014)
Very often computations on structural elements or machine components subjected to variable loading require using an advanced finite element model. This paper reports the numerical implementation of a model for multiaxial cyclic elasticplastic behaviour developed to extend the tools of the local deformation method under fatigue to multiaxial conditions. A basic computer code for axialtorsional loads was developed with the commercial software Matlab and a more sophisticated code based on the finite element model for general multiaxial loads was developed as a UMAT subroutine in Abaqus. Stress integration was introduced in the two usual forms: implicitly and explicitly. A comparison of the results obtained with the implicit and explicit formulations revealed that, under certain loading conditions, the outcome of the process depends on the particular integration scheme used.
Keywords: Cyclic plasticity